Relatório de Estágio Profissional "O auge de um sonho de criança" - Vitor Manuel Ferreira Pinto (2017)
The professional stage was the culmination of a child's dream which was lived in a real context, where I was able to put into practice the knowledge that I acquired in my initial formation. In order to get knowledge about the student-trainee and understand how he related all the knowledge acquired in theory and applied it into practice, a professional report was made. That report was made not only to perceive how he applied the knowledge, but to perceive what new experiences came from the teaching. The student's report was also made to reflect the road that was taken as well as the successive reflections that have been made throughout the year. The report tis organized in six chapters. The first one is Introduction which shows, in a succintly way, what I will develop throughout this report. The second one is the Personal Dimension, which is translated in a framework autobiographical and is the space where I talk about my initial expectations comparing them with the reality that I had lived. The third one is the Framework of the Professional Practice and is where I define the context of practice in which I have been inserted, as well as the characterizations of the classes, training group, cooperating teacher and guiding teacher. In the Operational Framework I reflected on what was done in practice, the problems, the strategies used, how was the reflective process and the new experiences, and is subdivided into three major areas: "Area 1 - organization and management of teaching and learning", which concerns the design of education, planning, implementation and evaluation; "Area 2 - Participation in school and community relations", which refers to the activities carried out and participation in the community; "Area 3 - Professional Development". The fifth chapter is devoted to the study "Attitude of students in relation to Physical Education - comparison between 6th and 11th year of schooling" and, finally, the sixth chapter that refers to "Conclusions and perspectives for the future". Key words: